2016
DOI: 10.1038/ncomms11105
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and stable perovskite solar cells prepared in ambient air irrespective of the humidity

Abstract: Poor stability of organic–inorganic halide perovskite materials in humid condition has hindered the success of perovskite solar cells in real applications since controlled atmosphere is required for device fabrication and operation, and there is a lack of effective solutions to this problem until now. Here we report the use of lead (II) thiocyanate (Pb(SCN)2) precursor in preparing perovskite solar cells in ambient air. High-quality CH3NH3PbI3−x(SCN)x perovskite films can be readily prepared even when the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
385
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 524 publications
(400 citation statements)
references
References 46 publications
11
385
1
3
Order By: Relevance
“…Tai et al, also claimed to have excellent moisture stability by incorporating a lead (II) thiocyanate (Pb(SCN) 2 ) via a two-step sequential deposition. [130] The introduced SCN − with ionic radius of (0.215-0.22 nm) is comparable to that of I − (0.22 nm), therefore there is some possibility for SCN − to replace I − in the perovskite lattice. They proposed that the SCN − tends to align along the same direction as CH 3 [131,132] Smith et al and Cao et al reported that by partial substitution of MA + cation with long-chain organic cations, the moisture stability of the perovskite materials has notably improved.…”
Section: Stabilitymentioning
confidence: 99%
“…Tai et al, also claimed to have excellent moisture stability by incorporating a lead (II) thiocyanate (Pb(SCN) 2 ) via a two-step sequential deposition. [130] The introduced SCN − with ionic radius of (0.215-0.22 nm) is comparable to that of I − (0.22 nm), therefore there is some possibility for SCN − to replace I − in the perovskite lattice. They proposed that the SCN − tends to align along the same direction as CH 3 [131,132] Smith et al and Cao et al reported that by partial substitution of MA + cation with long-chain organic cations, the moisture stability of the perovskite materials has notably improved.…”
Section: Stabilitymentioning
confidence: 99%
“…In contrast, the MAPb(SCN) 2 I reflection value increased slightly under the same humidity for 4 h. Moreover, the color of the MAPbI 3 film was almost completely changed to yellow in air for 30 d, indicating the formation of PbI 2 , whereas no significant change was observed for MAPb(SCN) 2 I. When exposed to 95% relative humidity air, the PCE of MAPbI 3 ‐based device decreased from 8.8 to 6.9% in 7 d and completely decomposed in 14 d, while that of the MAPb(SCN) 2 I‐based device only decreased from 8.3 to 7.4% in 14 d. Yan and co‐workers also prepared a stable MAPbI 3− x (SCN) x in humidity air 59. The average PCE of perovskite devices was 13.49%, and the maximum PCE exceeded 15%, even when the relative humidity kept 70% over 500 h. Calculations showed that the introduction of SCN − groups into the perovskite lattice was thermodynamically stable.…”
Section: Perovskite Layermentioning
confidence: 99%
“…This superior moisture tolerance was further confirmed by Tai and coworkers. [191] The introduction of SCN − allowed for preparation of high quality PVSK films even in high humidity environments (exceeding 70% RH). The devices exhibited excellent long-term stability features, even after more than 500 h ageing in humid air without encapsulation, maintaining the majority of its initial efficiency (>85%).…”
Section: F − or Pseudohalide/i Mixed Pvskmentioning
confidence: 99%